2013
DOI: 10.1186/2193-1801-2-603
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 10 km swimming performance of elite male and female open-water swimmers

Abstract: This study investigated trends in performance and sex difference in swimming speed of elite open-water swimmers at FINA 10 km competitions (i.e. World Cup races, European Championships, World Championships and Olympic Games). Swimming speed and sex difference in swimming speed of the fastest and the top ten women and men per event competing at 10 km open-water races between 2008 and 2012 were analysed using single and multi-level regression analyses. A total of 2,591 swimmers (i.e. 1,120 women and 1,471 men) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
49
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(56 citation statements)
references
References 39 publications
1
49
5
1
Order By: Relevance
“…In elite open-water swimmers competing in the 10 km FINA competitions between 2008 and 2012, swimming performances and sex differences in performance remained stable for the fastest elite open-water swimmers (Vogt, Rüst, Rosemann, Lepers, & Knechtle, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In elite open-water swimmers competing in the 10 km FINA competitions between 2008 and 2012, swimming performances and sex differences in performance remained stable for the fastest elite open-water swimmers (Vogt, Rüst, Rosemann, Lepers, & Knechtle, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The performance of elite open-water swimmers competing at world class level is well investigated (Vogt, Rüst, Rosemann, Lepers, & Knechtle, 2013, Zingg, Rüst, Rosemann, Lepers, & Knechtle, 2014b. However, performance of age group open-water swimmers competing in different age groups at world class level is not known.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the performance progression of the 10-km marathon swim event over the past 4 years has identified that swimmers reach speeds of up to 1.75 m/s or close to their maximal efforts after long periods of submaximal work (Vogt et al, 2013). Training strategies that adapt the muscle to maximize the contribution of fat to energy production during such swimming are encouraged (see Mujika et al, 2014).…”
Section: Energy Provision During Racing Carbohydrate For Open-water Pmentioning
confidence: 99%
“…Finally, in 2008 the 10 km open water swimming event was included in the Olympic Games. This led to swimmers training professionally under the supervision of qualified coaches (Vogt, Rust, Rosemann, Lepers, & Knechtle, 2013) and to a rise in the number of scientific studies in the context of these events. Nonetheless, much of the research on open water swimming events has centred on "extreme" competitions (Eichenberger, et al, 2012(Eichenberger, et al, , 2013Munatones, 2011;Ulsamer, Rüst, Lepers, & Knechtle, 2014).…”
Section: Introductionmentioning
confidence: 99%